PENGARUH KEBAHAGIAAN TERHADAP KINERJA KARYAWAN - Lukman Lukman; Nabilla Azqila Zalsabilla; Andi Salsabil Sevira; Andi Syairah Nabilah Cahyani (CV SWA Anugerah, 2024)
This study aims to analyze the effect of happiness on employee performance at PT. PLN (Persero) UID Sulselrabar. This study uses a quantitative approach with 15 employees from Division X as subjects. The instruments used are the Oxford Happiness Questionnaire (OHQ) to measure happiness and the Individual Work Performance Questionnaire (IWPQ) to measure employee performance. Data analysis was carried out using a correlation test and with SPSS 25 software. The results showed that the p-value for the relationship between happiness and employee performance was 0.329, which is greater than the significance level of 0.05. This indicates that there is no significant relationship between happiness and employee performance. Factors such as small sample size, homogeneity of research subjects, and the possibility of other variables that affect performance, such as work pressure or incentives, may be the reasons for the insignificance of this relationship. This study provides insight that happiness is not the only factor that determines employee performance in this organization. Further research with a more comprehensive approach and a larger sample size is recommended to explore other factors that affect performance.